Metodologi Pembelajaran Tafsir bil Ma’thūr: Integrasi Sumber Otoritatif dan Pembelajaran Kontemporer - Salam, Abdul; Nailil Murod, Miftahun; Solahudin (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to analyze the learning methodology of Tafsir bil Ma’thur by integrating authoritative sources with contemporary learning approaches. Tafsir bil Ma’thur is an exegetical method based on the Qur'an, the Sunnah, and the narrations of the Companions and the Tabi'in as primary authoritative sources. Amid the rapid advancement of information technology and the transformation of educational paradigms, an instructional model is required that preserves the authenticity of these sources while addressing the learning needs of contemporary students. This research employs a library research method with a descriptive-analytical approach. The data were collected from classical Qur'anic exegesis works, books on Qur'anic interpretation methodology, scholarly journal articles, and other relevant literature, and were analyzed using content analysis. The findings indicate that integrating authoritative sources with active, collaborative, and technology-assisted learning strategies enhances students' understanding of the principles of Tafsir bil Ma’thur without compromising the validity of transmission (sanad) and the authority of narrations. Furthermore, this approach promotes critical thinking, digital literacy, and academic attitudes in Qur'anic studies. Therefore, the learning methodology of Tafsir bil Ma’thur should be developed through pedagogical innovations while maintaining the epistemological foundations of classical Qur'anic exegesis to ensure its relevance in contemporary Islamic education.